2019
DOI: 10.1161/circulationaha.118.037137
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Year Trends and Sex Differences in Young Adults Hospitalized With Acute Myocardial Infarction

Abstract: Background: Sex differences are known to exist in the management of older patients presenting with acute myocardial infarction (AMI). Few studies have examined the incidence and risk factors of AMI among young patients, or whether clinical management differs by sex. Methods: The Atherosclerosis Risk in Communities (ARIC) Surveillance study conducts hospital surveillance of AMI in 4 US communities (MD, MN, MS, and NC). AMI was classified by physician review, using a validated algorithm. Medications and procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
315
0
28

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 515 publications
(359 citation statements)
references
References 36 publications
16
315
0
28
Order By: Relevance
“…Among patients with type 2 diabetes, which comprises more than 90% of all diabetes cases, women with type 2 diabetes were shown to be more likely obese, hypertensive and have hypercholesterolaemia but were less likely to be prescribed lipid-lowering medication and antihypertensive drugs, especially if they had cardiovascular disease in comparison with men [50]. Moreover, it was shown that admissions for acute myocardial infarctions steadily increased in the last two decades especially in younger patients whose history of diabetes and hypertension increased in parallel [51]. The proportion attributable to younger women was particularly high who also had lower probability of receiving guideline-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with type 2 diabetes, which comprises more than 90% of all diabetes cases, women with type 2 diabetes were shown to be more likely obese, hypertensive and have hypercholesterolaemia but were less likely to be prescribed lipid-lowering medication and antihypertensive drugs, especially if they had cardiovascular disease in comparison with men [50]. Moreover, it was shown that admissions for acute myocardial infarctions steadily increased in the last two decades especially in younger patients whose history of diabetes and hypertension increased in parallel [51]. The proportion attributable to younger women was particularly high who also had lower probability of receiving guideline-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI), a serious form of coronary artery disease (CAD), is a significant cause of death worldwide, particularly in the elderly population [1]. Actually, the elderly AMI patients who may have poor prognosis could be greatly improved by timely and appropriate intervention measures [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 The number is estimated to triplicate by 2050 due to population aging and increase of cardiovascular diseases in younger population, related to adverse health behaviors. [1][2][3][4] Currently, there are different options for heart valve replacement therapy; the most commonly applied are mechanical and bio-prosthetic heart valves. Despite both heart valve therapies have good durability and hemodynamic performances in older patients, they present critical disadvantages which prevent their use for the treatment of young patients' dysfunctions.…”
Section: Introductionmentioning
confidence: 99%